Most talkative : stories from the front lines of pop culture - Cohen, Andy, 1968- (Henry Holt and Company, 2012)
The man behind the "Real Housewives" writes about his lifelong love affair with pop culture that brought him from the suburbs of St. Louis to his own television show.